Harnessing aromatic properties for sustainable bio-valorization of lignin derivatives into flavonoids - Si-Yu Zhu; Na Li; Zhi-Hua Liu; Ying-Jin Yuan; Bing-Zhi Li (Green Carbon, 2025)
Lignin represents the most abundant renewable aromatic source, while flavonoids are aromatic natural compounds with various health-promoting properties and superior biological activities. The bioconversion of lignin derivatives into flavonoids holds promising potential for both lignin valorization and flavonoid synthesis. In this review, we prospect sustainable, atom-economic functionalization routes from lignin-derived aromatics to flavonoids by leveraging lignin’s inherent aromaticity. The representative flavonoid biosynthesis routes had first been elaborated from lignin derivatives in detail. The functionalization reactions involved in incorporating lignin derivatives into flavonoid structure were summarized to promote lignin bioconversion and yield flavonoids with desirable properties. Harnessing the powerful engineering strategies, such as synthetic biology, machine learning, metabolic regulation, boost the flavonoid production in microbial cell factories, enhancing lignin valorization. Overall, lignin functionalization routes for flavonoid biosynthesis hold promise to achieve the feasibility of lignin valorization and the production of flavonoids, contributing significantly to the sustainable bioeconomy.